The Correlation between Ultrasonographic Morphology and Structure of the Left Atrial Appendage, Blood Flow Velocity, and Plasma Galectin-3 Levels with Thrombus Formation in the Left Atrial Appendage of Patients with Atrial Fibrillation: Correlation of Left Atrial Appendage Factors with Thrombus Formation - Zhao, Linghui; Li, Min; Zhang, Yuchen; Tang, Wenrui; Huang, Dawei; Zhou, Guanjin; Zhu, Bo; Han, Zhiqi; Zhu, Dingyue (Journal of Medical Biochemistry, 2024)
Background: To explore the correlation between left atrial appendage morphology, blood flow velocity and plasma galectin-3 and thrombosis in patients with atrial fibrillation. Methods: Patients with atrial fibrillation who received treatment and completed ultrasound examination in hospital from 2022 to December 2023 were enrolled. According to whether there was left atrial appendage thrombosis, the patients were divided into a control group (no left atrial appendage thrombosis was found) and a study group (left atrial appendage thrombosis was found). The morphology and structure of the left atrial appendage, blood flow velocity and plasma galectin-3 level were recorded，exploring its correlation with left atrium thrombosis. Results: A total of 330 patients with atrial fibrillation were enrolled, including 278 in the control group and 52 in the study group. Left group and the control group of morphological structure differences (P < 0.05). The main lobe length, ostial area, longest diameter, shortest diameter, left atrial appendage volume and left atrial volume in the study group were higher than those in the control group (P < 0.05). The left atrial appendage emptying velocity, filling velocity and left ventricular ejection fraction of the study group were lower than those of the control group, and the left ventricular end-diastolic diameter was higher than that of the control group (P < 0.05). Group of white blood cell count, neutrophils/lymphocyte ratio, plasma galactose lectin - 3 levels were higher than control group (P < 0.05). ROC curve analysis of left atrial appendage emptying velocity, left atrial appendage filling velocity, left atrial end-diastolic diameter and left atrial ejection fraction had higher diagnostic value (P < 0.05). Conclusion: Left atrial appendage morphology, blood flow velocity and plasma galectin-3 level are important factors to evaluate the risk of left atrial appendage thrombosis in patients with atrial fibrillation, which can be used for clinical diagnosis and decision-making.